Preliminary Study of Calorific Value Increase on Lignite Coal Using Dialkyl Carbohydrate Biosurfactant - Mahreni Mahreni; Mitha Puspitasari (The Journal of Pure and Applied Chemistry Research, 2020)
Indonesian coal consumption is dominated by a low-grade coal quality, and supplied from local coals mining which was composed of lignite. A technological breakthrough has to be main objective to convert low grade coal into upper-class coal. This paper reports on improving the quality of lignite coal by washing with biosurfactant. Di-alkyl carbohydrates were tested on coal sizes of 80, 64, 16 and 6 mesh. The optimum biosurfactant applied to increase the calorific value derived from brown algae, namely isopropyl stearate alginate (ISA) 0.5%. This was able to improve a calorific value of lignite coal up to 27722.74% or increased by 11%. The size of the coal also affects the calorific value of lignite coal. Four coal sizes applied in the study (80, 64, 16, and 6 mesh), indicates coal size 80 mesh has given the best calorific value improvement. Conversely, the smaller of the coal size, increase biosurfactant absorption. Thus, improve the washing capability of biosurfactants.